Food anxiety and glycosylated hemoglobin among adults with type 2 diabetes mellitus treated at a medical center, Lima, 2023 - Hilario Meza, Yomira Katty (2025)
Objective: To evaluate the association between food anxiety and glycosylated hemoglobin (Hb) among adults with type 2 diabetes mellitus (T2DM) treated at a medical center in Lima in 2023. Materials and methods: This was a quantitative, non-experimental, cross-sectional, correlationalcausal study conducted in 2023. The sample consisted of 122 participants, comprising adults of both sexes, aged between 40 and 59 years, diagnosed with T2DM, who had undergone laboratory tests for glycosylated Hb within the past three months and who signed an informed consent. Those who had other comorbidities or were undergoing psychological treatment were excluded. Food anxiety was assessed using the Food Cravings Questionnaire–Trait instrument, which categorizes food anxiety into two levels: low (≤ 126 points) and high (> 126 points). Glycosylated Hb levels were measured through laboratory tests and classified into controlled, moderate, high, very high and critical. A descriptive analysis was performed using frequency measures such as numbers, percentages, median and interquartile range (IQR), while the association between variables was assessed using the chi-square test. Results: Evidence showed that 1.1 % had controlled glycosylated Hb, 13.2 % had moderate glycosylated Hb, 29.7 % had high glycosylated Hb, 33 % had very high glycosylated Hb and 23.1 % had critical glycosylated Hb. Almost all patients lacked adequate control of glycosylated Hb, while 53 % and 38 % had high and low levels of food anxiety, respectively. Participants with a high level of food anxiety exhibited higher values of glycosylated Hb. Food anxiety was more pronounced in men, who also had higher levels of glycosylated Hb (high, very high and critical). Conclusions: An association was found between food anxiety and glycosylated Hb.